2013
DOI: 10.1186/1475-2891-12-127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term fructooligosaccharide intake on equol production in Japanese postmenopausal women consuming soy isoflavone supplements: a pilot study

Abstract: BackgroundRecent studies suggest that some of the clinical effectiveness of soy or daidzein, which is a type of isoflavone, may be attributed to a person’s ability to produce equol from daidzein. Equol, which is a metabolite of one of the major soybean isoflavones called daidzein, is produced in the gastrointestinal tract by certain intestinal microbiota where present. Habitual dietary patterns may alter the intestinal bacterial profile, and influence the metabolism of isoflavones and the production of equol. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 40 publications
0
11
1
Order By: Relevance
“…Previous clinical trials assessing an FOS intake of ≤10 g/day have been reported for adult women [31,32,33,34,35]; however, the number of reports on FOS perinatal ingestion in women has reduced [17]. In the present study, we found no differences in the frequency of abdominal symptoms in the FOS group compared with those in the placebo group until 10 weeks after the start of the intervention.…”
Section: Discussioncontrasting
confidence: 68%
“…Previous clinical trials assessing an FOS intake of ≤10 g/day have been reported for adult women [31,32,33,34,35]; however, the number of reports on FOS perinatal ingestion in women has reduced [17]. In the present study, we found no differences in the frequency of abdominal symptoms in the FOS group compared with those in the placebo group until 10 weeks after the start of the intervention.…”
Section: Discussioncontrasting
confidence: 68%
“…However, it might not be easy to enhance equol production in humans, especially in equol non-producers. Some prebiotic supplementations with soya have shown no effect on the equol-producing capacity in humans ( 52 , 53 ) . However, further studies are needed to confirm whether RS promotes equol production in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Not all but about 20%–35% of Western and 50%–55% Asian adult populations are Equol producers [16]. They can metabolize Daidzein by gut microflora to an estrogenic metabolite called Equol [7-hydroxy-3-(4′-hydroxyphenyl)-chroman], which exhibits biological properties that exceed those of its precursor [17,18,19,20]. Equol is similar in structure to the human female hormone, 17-β-estradiol [21].…”
Section: Introductionmentioning
confidence: 99%